O uso da Marca País na comunicação de empresas brasileiras no exterior - Nunes, Nádia Cristina Rodrigues (2014)
This study aims to identify the use of the components of the nation brand in communication efforts of the internationalized Brazilian companies. Seeks to examine whether there are industries that avoid the use of these elements and others, that use them as differential with competitors. The methodology to achieve the proposed objective uses a qualitative research to evaluate international communication, through international websites of several Brazilian companies who made their internationalization processes. Images in the international websites of the companies studied were collected, and the processing and analysis of data were performed by means of content analysis and semiotic analysis. The results of the field research showed that many Brazilian companies operating abroad do not have websites in the countries in which they operate. Companies that have developed international websites used elements of nation brand in relation to Brazil, but in a different proportion and frequency in relation to the study of nation brand adopted for the research. Other results were seen with respect to the industries that use the elements of the nation brand. Industries were perceived with greater propensity to use these elements and other industries that prevented the use of elements of nation brand. Unable to clearly establish, through study, whether Brazilian companies use, consciously, elements of nation brand as a differentiator against their competitors in international markets. The research results, however, could not be generalized because all internationalized Brazilian companies have not been studied, and future researches could expand the scope of this study. However, the results indicate trends of use of the elements of nation brand that can provide managers of Brazilian companies that already operate or will operate abroad, a differential relative to international competitors.